1984
DOI: 10.1037/0022-0663.76.6.1119
|View full text |Cite
|
Sign up to set email alerts
|

Semantic differential placement of attributions and dimensions in four different groups.

Abstract: The purpose of this study was to empirically validate subjects' classification of 11 attributions (mood, skill, knowledge, chance, effort, competence, help, ability, task, bias, luck) according to dimensions of locus, stability, controllability, predictability, and globality. The sample of 200 subjects (100 males and 100 females) consisted of 50 undergraduate education majors, 50 graduate education majors, 50 undergraduate psychology students, and 50 naive lay individuals (over 35 years of age) who had never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Heider, 1958;Langer, 1983;Palenzuela, 1988). Chandler and Spies (1984), asking their subjects to give Semantic Differential ratings of several attributional concepts, found 'luck' to score even lower than 'chance' on the dimensions of controllability and predictability, whereas Friedland (1992) claims that the idea of luck, as opposed to chance, 'elicits, at the very least, an illusion of control' (p. 267). Still, he agrees that belief in luck is distinguishable from belief in the causal efficiency of one's own behaviour.…”
Section: Study 1: Good and Bad Luck Experiences In Daily Lifementioning
confidence: 99%
“…Heider, 1958;Langer, 1983;Palenzuela, 1988). Chandler and Spies (1984), asking their subjects to give Semantic Differential ratings of several attributional concepts, found 'luck' to score even lower than 'chance' on the dimensions of controllability and predictability, whereas Friedland (1992) claims that the idea of luck, as opposed to chance, 'elicits, at the very least, an illusion of control' (p. 267). Still, he agrees that belief in luck is distinguishable from belief in the causal efficiency of one's own behaviour.…”
Section: Study 1: Good and Bad Luck Experiences In Daily Lifementioning
confidence: 99%
“…Several authors have suggested that subjects' own evaluation of causal dimensions is a better predictor of their cognitions, emotions, and behaviour than a priori evaluations (Benson, 1990;Chandler & Spies, 1984;Meyer, 1980;Weiner, 1983). Thus, from an attributional theory perspective, the most important aspects in causal attributions are their underlying dimensions (Graham, 1991).…”
mentioning
confidence: 97%
“…In the traditional attribution research literature it would be considered as internal and unchangeable. However, Chandler and Spies (1984) found that the meaning is sometimes embedded in competence, skill, or knowledge, suggesting that these are capable of being controlled and altered. Hence, attributions for failure to insufficient competence, skill, effort, and knowledge are constructive, empowering, and hopeful.…”
Section: Discussionmentioning
confidence: 99%